2012
DOI: 10.1590/s1516-05722012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Conteúdo polifenólico e atividade antioxidante dos frutos da palmeira Juçara (Euterpe edulis Martius)

Abstract: RESUMO:O conteúdo polifenólico e a atividade antioxidante do extrato do fruto de Euterpe edulis Martius foram avaliados. Esta espécie é uma palmeira conhecida como Juçara, nativa da Mata Atlântica e utilizada para a extração de palmito. O processo de extração do palmito acarreta a morte da planta, uma vez que esta apresenta estipe único. A elevada demanda ocasionou a escassez deste recurso natural. Muitas espécies da Mata Atlântica podem ser utilizadas pelo manejo sustentável para a preservação e exploração ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
(10 reference statements)
0
5
1
9
Order By: Relevance
“…The antioxidant activity and the anthocyanin and phenolic compound contents found in this study for juçara fruits native to southeastern Minas Gerais, were higher than those found for juçara fruits from other regions of Brazil (RUFINO et al, 2010;LIMA et al, 2012). This observation may be explained due to differences in maturation stage and in the storage and processing conditions of the fruits.…”
Section: Resultscontrasting
confidence: 70%
“…The antioxidant activity and the anthocyanin and phenolic compound contents found in this study for juçara fruits native to southeastern Minas Gerais, were higher than those found for juçara fruits from other regions of Brazil (RUFINO et al, 2010;LIMA et al, 2012). This observation may be explained due to differences in maturation stage and in the storage and processing conditions of the fruits.…”
Section: Resultscontrasting
confidence: 70%
“…Nota-se que um fruto que vem ganhando destaque, entre esses alimentos, é o açaí (Euterpe oleracea Mart. ), por apresentar em sua composição quantidades significativas de um grupo dos flavonoides, conhecido como antocianinas (LIMA et al, 2012;LIN et al, 2007).…”
Section: Muitos Países Utilizam Estratégias Preventivas Com Informaçõunclassified
“…Açaí fruit comes from a species of palm trees called Euterpe oleracea. The fruit of Euterpe edulis, known as juçara, is very similar to that of E. oleracea and is a promising source of antioxidants Costa, Garcia-Diaz, Jimenez, & Silva, 2013;Felzenszwalb, Marques, Mazzei, & Aiub, 2013;Iaderoza, Baldini, Draetta, & Bovi, 1992;Lima et al, 2012;Pacheco-Palencia, Duncan, & Talcott, 2008).…”
Section: Introductionmentioning
confidence: 99%